The Presentation of Victimization in Selected 2003 War Plays - Abd-Aun, Raad Kareem; Mohsin, Zaineb Raad (جامعة بابل - كلية التربية للعلوم الإنسانية, 2022)
يستخدم الاضطهاد لوصف العملية بأن تكون مجني عليه أو جاني. على الرغم من أن هذين المفهومين مرتبطان ببعضهما البعض، إلا أن لهما علاقات بالعديد من المجالات. ونتيجة ذلك، فإن الاضطهاد سوف يظهر في علاقته بحرب ٢٠٠٣ في العراق. سيحدث هذا من خلال تقديم مسرحيتين لكتابين مسرحيين مختلفين. يتم تناول كل مسرحية من منظور مختلف. مسرحية كم ميلا إلى البصرة؟ تتقصى الجرائم التي كانت تحصل في العراق ودور الإعلام في تغطية هذه الجرائم. بينما تدور مسرحية العودة حول عودة الجنود من منطقة الحرب وتأثير اضطراب ما بعد الصدمة على حياتهم وكذلك أسرهم. Victimization is used to describe the process to be a victim or a victimizer. Even though these two notions are related to each other, however, they have relations to many fields. Being so, victimization is going to be shown in its relation to the war of 2003 in Iraq. This is going to happen through presenting two plays by two different playwrights. Each play is tackled from a different perspective. That is to say, How Many Miles To Basra? Is exploring the crimes that were happening in Iraq and the role of media in reporting these crimes. Re-Entry is about the coming back of soldiers from the warzone and the effect of PTDS on their lives as well as their families.
Keywords: السياسة العراقية -- علم الجريمة -- الأدب المسرحي -- الحرب الأمريكية العراقية